The Impact Analysis of Macroeconomic Factors to Indonesia’s Export Performance - Mustofa, Hafidz Zainul; Faizin, Moh. (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2025)
Research Originality — This study provides an empirical analysis of the influence of macroeconomic factors on Indonesian exports in the short and long term. Unlike previous studies that tend to focus on one main variable, this study integrates several macroeconomic factors, namely foreign direct investment (FDI), exchange rate, inflation, interest rate, and gross domestic product (GDP), to evaluate their collective impact on Indonesia's export performance. By applying the Vector Error Correction Model (VECM), this study provides new insights into the dynamics of Indonesian exports from a macroeconomic perspective. Research Objectives — This study aims to analyze the influence of macroeconomic factors on Indonesian exports during the period 2007–2022. Specifically, this study examines the impact of FDI on export volume and value, the effect of exchange rate fluctuations on the competitiveness of export products, the correlation between inflation rate and export structure, the impact of interest rates on investment and exports, and the contribution of GDP to exports. Research Methods — This study uses a quantitative approach with the VECM model to analyze secondary time series data published quarterly during the period 2007–2022. Data were obtained from the Statistic Indonesia (BPS), the Ministry of Investment (BKPM), and Central Bank of Indonesia (BI). The analysis was conducted using E-Views 10 software to identify the short-term and long-term relationships between macroeconomic variables and Indonesian exports. Empirical Results — The results of the study indicate that FDI has an indirect positive impact on exports through changes in production structure and technology transfer. The exchange rate has a positive impact in the long term, but a negative impact on exports in the short term. Inflation has a positive effect on exports in the long term, but is not significant in the short term. Interest rates have a negative impact in both the short and long term, while GDP has a negative impact on exports in the long term, but a positive impact in the short term. Implications — The findings in this study have important policy implications for stakeholders in the economic sector. The proposed recommendations include providing incentives for foreign investment to increase export competitiveness, stable exchange rate management to reduce the impact of volatility, effective inflation control so as not to disrupt export competitiveness, interest rate policies that support the export sector, and economic growth policies that are oriented towards export market expansion.